PENGARUH KARAKTERISTIK PEMERINTAH DAERAH TERHADAP KEPATUHAN PENGUNGKAPAN WAJIB DALAM LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Empiris pada Kabupaten/Kota di Indonesia) - Suhardjanto, Djoko; Yulianingtyas, Rena Rukmita (JURNAL AKUNTANSI DAN AUDITING, 2011)
The purpose of this study is to examine the influence of local government characteristicstowards mandatory disclosure compliance of financial statement. Local governmentcharacteristics used in this research are size, the number of Satuan Kerja Perangkat Daerah(SKPD), type of local government. This research also used control variable such as the totalnumber of Parliament members and location of local government. This research focuses onthe disclosure compliance of balance sheet stated in SAP. 100 financial statements ofmunicipalities are chosen as samples, but there are only 51 samples that can be used in thisresearch. The results of descriptive statistic show that the average level of mandatorydisclosure compliance in Indonesian municipalities is 30.85%. The maximum level ofmandatory disclosure compliance in Indonesian municipalities is 50.88% (Kabupaten Sinjai),while the minimum level is 14.70% (Kota Sukabumi). The results of regression analysis showthat the number of parliament members as control variable (β = 0.090 and p-value of 0.049)are significant predictor for the level of mandatory disclosure compliance towards SAP, whilesize, the number of SKPD, and type of local government as local government characteristicsdoesn’t influence mandatory disclosure compliance of financial statement. The finding isexpected to have some contributions for local government’s, especially for policy makers andregulators. The implications of this study are the regents need to encourage the disclosurecompliance with SAP, and apply reward and punishment system regarding mandatorydisclosure.Keywords: mandatory disclosure, governmental accounting standard (SAP), localgovernment characteristics